9 Levels for Value systems Development of a scale for level-measurement - Thomas Dobbelstein; Rainer Krumm (Journal of Applied Leadership and Management, 2012)
How can the value levels of the 9 Levels for Value systems used in application-oriented personnel and organisational development be measured reliably?
Keywords: 650